Managing mobile platform power - Ogras, Umit Y.; Ayoub, Raid Z.; Kishinevsky, Michael; Kadjo, David (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2013)
Power consumption has been one of the major design considerations for more than a decade [6]. Hence, energy efficient techniques have been widely studied to harness the processing power within available power and thermal budgets [3][4][10]. With the proliferation of smart mobile devices, the criticality of energy efficiency is multiplied. On one hand, increasing computational power as well as sensing, storage, and communication capabilities open up wide range of power-hungry application domains. On the other hand, the battery life rises as one of the major concerns of the end user [9]. Furthermore, these fanless devices are subject to tight surface, or skin, temperature constraints which limit the peak power consumption, since the skin temperature directly affects the user experience (UX). As a result, power management techniques crafted specifically for smart mobile devices become necessary. In this paper, we review three differentiating aspects for managing the power of smart mobile devices. More specifically, we emphasize the importance of platform view, user experience and platform level optimization.